Kemampuan Pemecahan Masalah Matematis Mahasiswa PGMI Pada Materi Volume Bangun Ruang: PGMI Students' Mathematical Problem Solving Ability in Constructing Volume Material - Nurdiana Siregar (Jurnal Derivat: Jurnal Matematika dan Pendidikan Matematika, 2022)
Describing the mistakes that are often made by PGMI students in solving the mathematical problem solving ability test on the material of volumetric shapes is the basic goal of this research. This research belongs to the type of descriptive research with the object of research being fourth semester PGMI students at one of the State Universities (PTN) of North Sumatra province. The sample of data sources collected is 34 people with heterogeneous ability levels. The data source collection instrument was carried out using an essay test. The flow of data analysis is carried out by reducing the data then presenting the data in the form of tables and figures, finally drawing conclusions. The results of this study revealed that the error experienced by students was in understanding the concept of volume incorrectly and it was assumed that they were unable to distinguish the concept of surface area from volume. The next aspect is the lack of accuracy in understanding the text of the question which ultimately solves the problem with wrong perceptions, the answers are not arranged logically and systematically with the stages of problem solving, and errors at the counting stage in getting the final answer. Keywords: Error Analysis; Problem solving skill; Geometry